COVID-19 vaccine acceptances and barriers to vaccination in the context of Kerala: a cross-sectional survey - Sunil, Sreemol; R., Anish K.; J., Sreekutty M. (International Journal Of Community Medicine And Public Health, 2021)
Background: The long-term control of the pandemic COVID-19 pandemic hinges on the uptake of vaccine and high immunization uptake is critical but barriers to immunization exists. Vaccine hesitancy is one of the top 10 threats to global health. Hesitancy will be a challenge to curbing this pandemic. Apt vaccination strategies are very essential to increase vaccine acceptance. Methods: A cross‐sectional study among the population in Kerala where data was collected through an online questionnaire using Google forms and was distributed using social media platforms. Total of 213 data was collected. Study focused on aspects of vaccine communication, preference of COVID-19 vaccine, perceived benefits, and barriers of COVID-19 vaccine acceptance and cues of vaccine. Results: 80.2% of the respondents were willing to get vaccinated. 78.9% of the respondents have taken previous vaccinations by the government. 70 of them trust government health care departments and media (82.2%) is the least trusted platform regarding vaccination. 56.3% are not getting enough information on COVID vaccine safety, while 81.2% of the respondents did not receive negative information. A majority of them (64.3%) relied on official government websites for information. Majority agrees to the perceived benefits of COVID-19. 80.3% are willing to take free vaccination. 46.9 % are willing to pay for COVID vaccine. Conclusions: The scenario in Kerala is positive towards the vaccination drive and majority of them are willing to get vaccinated. But strategies must be made effective in terms of elevating the barriers to vaccination.